"Melanocytic Nests Arising in Lichenoid Inflammation": Reappraisal of the Terminology "Melanocytic Pseudonests". (December 2015) - Chung, Hye Jin; Simkin, A. David; Bhawan, Jag; Wolpowitz, Deon
Abstract : Abstract: Pseudonests or pseudomelanocytic nests represent aggregates of cells and cell fragments, including keratinocytes, macrophages, lymphocytes, and occasional melanocytes. Pseudomelanocytic nests in the setting of lichenoid inflammation can mimic atypical melanocytic proliferations. Several reports documented nonspecific staining of pseudonests with melanoma antigen recognized by T cells-1/Melan-A, which can be detected in the cytoplasm of nonmelanocytic cells. In contrast, nuclear stains, such as MITF and SOX10, avoid this nonmelanocyte cytoplasmic staining. The authors have previously proposed the term melanocytic pseudonests to describe junctional nests with numerous (>2) true melanoma antigen recognized by T cells-1/Melan-A, SOX10, and MITF in a nonmelanocytic lesion with lichenoid inflammation (unilateral lichen planus pigmentosus/erythema dyschromicum perstans). In this study, the authors report another case of this phenomenon arising in a different lichenoid inflammatory dermatitis (lichen planus). The immunophenotype and number of clustered true melanocytes indicate that these dermoepidermal aggregates represent true melanocytic nests and not pseudonests of any type. Therefore, the authors propose the revised terminology of "melanocytic nests arising in lichenoid inflammation" to describe this novel pattern of benign melanocytic reorganization or proliferation in a subset of lichenoid dermatitides. Because this phenomenon can mimic atypical melanocytic proliferations, clinicopathologic correlation is essential for the correct diagnosis.